Transforming Learning Independence in Future Science Teachers: The Powerful Impact of a Project-Based Collaborative Learning (PjBCL) Model - Mohan Taufiq Mashuri; Mia Aina; Eka Setiawati; Ihwana As’ad; Nor Syamimi Mohamed Adnan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study examines the transformative impact of the project-based collaborative learning (PjBCL) model on the learning independence of prospective science teachers. As the educational paradigm shifts toward a learner-centered approach, efforts to foster independence and responsibility for learning in prospective educators are becoming increasingly important. This study employed a quasi-experimental design with a mixed-methods approach, involving 64 students from the science education study program who were enrolled in a course on developing science teaching materials. Students were divided into an experimental class and a control class. The experimental class participated in a series of project-based collaborative learning (PjBCL) activities, while the control class received regular instruction. Data on learning independence were collected through self-regulated learning (SRL) questionnaires, reflective journals, and classroom observations. The results showed a significant increase in the prospective teachers' ability to plan, coordinate, and implement their learning process independently in the experimental class. Furthermore, the collaborative nature of this model encouraged shared accountability, peer support, and active involvement of all students, which overall formed a more independent learning mindset. This study demonstrates the effectiveness of a project-based collaborative learning model in preparing prospective science teachers who are independent, reflective, and innovative.